Optimization of Bench Width and Vertical Bench Position for Claystone Slopes Using the Limit Equilibrium Method under a Safety Factor Constraint - Putra, Kyrie Eleison; Aditya, Fariz; Heriyadi, Bambang; Anarta, Rudy (UIR PRESS, 2026)
One important aspect of open pit mine planning is slope geometry design, which affects the stability of the slope and the efficiency of overburden removal. This study aims to investigate the influence of vertical bench position and bench width on slope stability and their effect on stripping volume. The limit equilibrium method was used for slope stability analysis, with the assistance of Rocscience Slide2 software. The stripping volume estimate was obtained from pit shell simulations using GEOVIA Surpac software. The vertical bench positions analyzed were ¼, ½, and ¾ of the total slope height, which was 60 m. The bench width variations tested were 0, 5, 10, 15, 20, and 25 m, while maintaining a minimum safety factor requirement of 1,3. The analysis indicated that the optimal configuration is achieved by placing the bench at the vertical position of ½ of the overall slope height with a bench width of 10 m, which results in an overall slope angle of 44°. The result is steeper than the no-bench scenario, with an overall slope angle of 42°. This geometry produces an estimated overburden volume of 195,123,000 m3, which is smaller than the no-bench scenario of 196,559,500 m3. Therefore, the reduction in stripping volume is 1,436,500 m3 or approximately 0.73%. This study shows that optimizing the bench configuration enables the implementation of steeper overall slope angles while reducing the required stripping volume in open pit mine planning.